School Performance and Young Adult Crime in a Brazilian Birth Cohort - Martins, Rafaela Costa (Journal of developmental and life-course criminology, 2022)
Poor school performance may increase the risk of crime and violence via effects on self-esteem, risky behaviours, peer networks, and perceived stakes in society. Despite very high rates of violence in Latin America, no longitudinal research has addressed this issue in the region. Two aspects of educational performance (grade repetition and school completion) were examined during adolescence in a population-based Brazilian birth cohort study (n = 3584). Violent and non-violent crime were measured at age 22 years in confidential self-reports; sociodemographic, family, and individual confounders were measured between birth and age 11 years, and potential mediators were measured at age 18 years. The prevalence of violent and non-violent crimes at 22 years was 8.2% and 3.3%, respectively, referring to acts in the previous twelve months. For youth repeating school grades three times or more, the odds of violent crime were 2.4 (95%CI: 1.6–3.6) times higher than for those who had not repeated any school grade. Youth completing school had a lower risk for both violent (OR = 0.5; 95%CI: 0.4–0.7) and non-violent crime (OR = 0.3; 95%CI: 0.2–0.5), compared to those who did not finish school by the expected age. The protective effect of completing school was independent of the number of grades previously repeated. In conclusion, repeating school grades was associated with increased risk for crime; however, successfully managing to complete school by the expected age was an important protective factor against crime, even after multiple grade repetitions.